FEATURES OF ANTI-CAFE INTERIOR DESIGN WITH THE PRESENCE OF ANIMALS - ПОПОВА , І.І. (Art and Design, 2022)
Purpose. The aim of the work is to determine the features of the interior design of the anticafe with the presence of animals and the subject content of the cat café environment. analyze the experience of designing an anticafe in the context of creating a common space for visitors and animals by means of design. Methodology. The study is based on systems and environmental approaches that allow us to consider the interior space and subject environment of the cafe as a holistic project. The study used: the method of systematic analysis of specialized resources and scientific publications on the research topic; method of comparative analysis of similar objects; generalization of the information received in the course of research. The source base of the research was scientific and journalistic articles, domestic and foreign design developments of cat café spaces, catalogs of designer furniture and equipment for pets. Results. Experience and trends in interior design of cat café as an example of anticafe format with the presence of animals in different countries are considered. The main functional groups of the subject content from the point of view of human and animal interaction are analyzed. The peculiarities of the formation of the stylistics of the interior of the premises of the cafe are considered, the connection between the space of man and the space of animals in the design – interior solutions. Scientific novelty. The peculiarities of designing the interiors of anti-cafes with the presence of animals are determined. Practical significance. The research is conditioned by the expansion and deepening of knowledge about the formation of the design of anti-cafe environments with the presence of animals and filling them with equipment that provides the opportunity and can be used in the practice of designing appropriate environments.